Evaluating the Effectiveness of Backward Design in Enhancing Formative Assessment Practices - Mousa, Mojahed (Journal of Pedagogy and Education Science, 2025)
The research investigates backward design implementation in formative assessment practices to determine its effects on instructional effectiveness, student engagement, and curriculum coherence. It employed a mixed-methods design to gather data from 26 in-service teachers who specialized in STEM and English as a Foreign Language at public, private, and UNRWA schools in Palestine. The research used a combination of structured questionnaires and follow-up interviews to obtain both quantitative and qualitative data. Results showed that teachers acknowledge backward design benefits, which include better student comprehension and improved assessment-objective alignment and student motivation, yet they faced implementation difficulties. Teachers indicated that backward design planning led to increased student participation, better critical thinking abilities, and stronger student ownership of their learning. The participants suggested three modifications to backward design, which included adaptable templates, lighter curriculum requirements, and student reflection integration. The research indicates backward design shows potential to improve formative assessment, but its successful implementation needs specific professional development and contextual modifications. It also demonstrates backward design's value for teaching and learning, yet emphasizes the necessity of combining it with conventional curriculum methods in various educational contexts.